COGNITIVE DISSONANCE: ROLES IN CONTRADICTION IN CONSCIOUSNESS - Sardorbek Kholmukhammedov (Scholar Express Journals, 2025)
Cognitive dissonance, a pivotal concept in psychology, refers to the psychological discomfort caused by holding conflicting beliefs, values, or attitudes simultaneously. This concept, formally introduced by Leon Festinger in 1957, has gained widespread recognition for its applicability in various fields such as social psychology, behavioral economics, and marketing. While commonly understood as internal conflict, cognitive dissonance is a complex phenomenon influencing decision-making, emotional regulation, and interpersonal interactions. This article delves deeply into the historical origins of cognitive dissonance, its empirical validation, and its implications in societal, cultural, and business contexts. Drawing on the aftermath of the 1934 Nepal– India earthquake, Festinger’s experimental studies, and contemporary issues in telecommunications, this study underscores the enduring relevance of cognitive dissonance in understanding human behavior.
Keywords: Cognitive Dissonance; perceptual distortion; historical origin of cognitive dissonance